Mappings: cartographies for the complexity of the contemporary maritime landscape - Matni, Olivia (2022)
This article proposes an analysis on cartography for the complexity of contemporary landscapes in maritime horizons. By discussing a concept of landscape from Jean-Marc Besse in Voir la Terre. Six essais sur le paysage et la géographie (2006), the landscape is comprehended as a desire to see, as an image of subjectivities in the relationship between man-territory, as a support and matter for existence and as an emotional, biological, political and symbolic place. Subsequently, it is presented a consideration on Cartography through a brief analysis of its historical process, trough the synthesis it performs as well as its geographic, political, social, cultural and symbolic complexity. As following, we observe the cartographic project ''The Poveiro Sea'' and ''their Maritime Backyard'' (2020) by José Pedro Fernandes as a visibility tool, where the author approaches the cartographic exercise trough the observation of location methods and by mapping empirical procedures developed by a group of fishermen from Póvoa do Varzim. We conclude this analysis with the work A Maritime Portrait of Ílhavo (2021) that was commissioned by the Municipality of Ílhavo to the University of Minho, developed by the architect André Tavares who created a series of maps that synthesize the landscape changes at the Port of Barra within the last 100 years, exposing the territorial alterations trough the ocean's point of view. With this text, we intend to propose a support analysis with the further objective of organizing a series of cartographies for the biogeographic landscape of Ílhavo, a municipality culturally and historically connected to maritime activities.